WATCH AFib: smartwatches for detection of atrial fibrillation in secondary prevention of cryptogenic stroke—protocol for a prospective, intraindividual-controlled, multicentre clinical study - Penkert, Horst; Härtl, Johanna; Hapfelmeier, Alexander; Egert-Schwender, Silvia; Heimsch, Edith; Friedenberg, Sabine; Müller, Alexander; Hahn, Franziska; Martens, Eimo; Wunderlich, Silke (Frontiers in Neurology, 2025)
RationaleDetection of atrial fibrillation (AFib) and subsequent anticoagulation therapy reduce the risk of recurrent stroke, while prolonged rhythm monitoring significantly increases AFib detection. Thus, prolonged smartwatch-based ECG monitoring after cryptogenic ischemic stroke or transient ischemic attack (TIA) could lead to a reduction of recurrent stroke by prompting adequate anticoagulation therapy.AimWATCH AFib investigates the accuracy of smartwatches for AFib detection in patients with cryptogenic TIA or ischemic stroke compared to an implantable event recorder.Sample size40 cases of AFib are required to estimate the sensitivity for AFib detection per patient with a precision of about 10%. As AFib is observed in 9%−16% of cryptogenic strokes, we intend to enroll 400 patients.MethodsWATCH AFib is a prospective, intraindividual-controlled, multicentre clinical study in patients with cryptogenic ischemic stroke or TIA. ECG-data from smartwatches and event recorders is continuously monitored by two independent cardiologists for a follow-up period of 6 months. If AFib is detected, therapeutic options are discussed at the including center.Primary outcomeTo compare smartwatch- and event recorder- based sensitivity and specificity of AFib detection per patient after 6 months.DiscussionProlonged AFib screening after stroke is currently suboptimal. Smartwatches might be a non-invasive, cost-effective, widely available alternative for prolonged rhythm monitoring. Usability in severely affected patients and patients with persisting neurological deficits might be limited.Trial registrationThe study is registered on clinicaltrials.gov. Registration number: 20230726.